2006
DOI: 10.1677/erc.1.01322
|View full text |Cite
|
Sign up to set email alerts
|

Role of receptor complexes in the extranuclear actions of estrogen receptor α in breast cancer

Abstract: Our recent studies have examined the role of various receptor complexes in the mediation of rapid, extranuclear effects of estradiol. This review describes 17b-estradiol (E2)-initiated extranuclear signaling pathways, which involve the insulin-like growth factor 1 receptor (IGF-1R) and epidermal growth factor receptor (EGFR) and result in the activation of several kinase cascades. The biologic results of these effects are the enhancement of cell proliferation and diminution of programmed cell death (apoptosis)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 69 publications
3
58
1
Order By: Relevance
“…Activation of AKT and overexpression of EGF and ERBB receptors are consistent with previous observations in MCF7-LTED cells and related breast cancer conditions (Masamura et al, 1995;Jeng et al, 1998;Shim et al, 2000;McClelland et al, 2001;Knowlden et al, 2003;Osborne et al, 2005;Yue et al, 2005;Song et al, 2006;Beeram et al, 2007;LewisWambi et al, 2008;Santen et al, 2008;Ghayad et al, 2009). Notably, ERBB2 amplification was associated with resistance to endocrine therapies (Ellis et al, 2006), and treatment with the mTOR inhibitor RAD001 increased letrozole efficacy in a neoadjuvant setting of ERa-positive breast cancer (Baselga et al, 2009).…”
Section: Resultssupporting
confidence: 85%
“…Activation of AKT and overexpression of EGF and ERBB receptors are consistent with previous observations in MCF7-LTED cells and related breast cancer conditions (Masamura et al, 1995;Jeng et al, 1998;Shim et al, 2000;McClelland et al, 2001;Knowlden et al, 2003;Osborne et al, 2005;Yue et al, 2005;Song et al, 2006;Beeram et al, 2007;LewisWambi et al, 2008;Santen et al, 2008;Ghayad et al, 2009). Notably, ERBB2 amplification was associated with resistance to endocrine therapies (Ellis et al, 2006), and treatment with the mTOR inhibitor RAD001 increased letrozole efficacy in a neoadjuvant setting of ERa-positive breast cancer (Baselga et al, 2009).…”
Section: Resultssupporting
confidence: 85%
“…This suggests that AR might be recruited to membranes by other membrane proteins, thereby facilitating the flow of signals from AR to Akt and possibly to other signaling proteins. Consistent with this idea, ER␣ was found to be capable of activating signaling from the insulin-like growth factor-1 receptor by a mechanism involving direct binding of ER␣ to the insulinlike growth factor-1R (45). Post-translational modifications, such as phosphorylation (46) or palmitoylation (47), would be another mechanism by which AR might be recruited to membrane sites.…”
Section: Discussionmentioning
confidence: 84%
“…2B, top panel) and in xenografts (data not shown) and were inhibited by the pure antiestrogen, fulvestrant. 8,11 We further demonstrated that activated MAP kinase is implicated in the enhanced growth of LTED cells since inhibitors of MAP kinase such as PD98059 or U-0126 block the incorporation of tritiated thymidine into DNA. 7 To demonstrate proof of the principle of MAP kinase participation, we stimulated activation of MAP kinase in wild type MCF-7 cells by administering TGFα (data not shown).…”
Section: Phenomenon Of Hypersensitivity: Mechanisms and Pathwaysmentioning
confidence: 87%